2010
DOI: 10.1038/ejcn.2010.158
|View full text |Cite
|
Sign up to set email alerts
|

Trends in adherence to the Mediterranean diet in an Italian population between 1991 and 2006

Abstract: Background/Objectives: The aim of this study is to investigate whether adherence to the Mediterranean diet changed during the period [1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006] in an Italian population. Subjects/Methods: We derived data from the comparison groups of a network of case-control studies on cancer and acute myocardial infarction conducted in the greater Milan area between 1991 and 2006. Subjects were 3247 adults (1969 women, 1278 men; median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
25
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
10
25
0
2
Order By: Relevance
“…Although it is difficult to discriminate the influence on health of habitual physical activity from that of diet, we did not observe any significant independent effect of physical activity on the outcomes considered in our study. Furthermore, our study found that adherence to a Mediterranean dietary pattern was associated with both a higher level of education and age, thus confirming what was recently reported in Italian cohorts, 44,45 as well as confirming the importance of biosocial influences on dietary habits. This study has several limitations.…”
Section: Discussionsupporting
confidence: 93%
“…Although it is difficult to discriminate the influence on health of habitual physical activity from that of diet, we did not observe any significant independent effect of physical activity on the outcomes considered in our study. Furthermore, our study found that adherence to a Mediterranean dietary pattern was associated with both a higher level of education and age, thus confirming what was recently reported in Italian cohorts, 44,45 as well as confirming the importance of biosocial influences on dietary habits. This study has several limitations.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, it has been documented in many previous studies that different educational groups have healthier food choices (i.e. more adherent to the MD) probably due to increased nutrition knowledge and increased motivation to follow healthy lifestyles (6,13,(25)(26)(27)(28) . We confirmed the aforementioned trend, since participants in the medium educational category, mostly representative in the urban sample, were more likely to adhere to the MD compared with participants in the lower educational category.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet, characterized by a high monounsaturated/saturated fat ratio, a relatively high consumption of cereals, legumes, fruit and vegetables, and fish, a moderate consumption of alcohol, and a low consumption of meat and meat products, and milk and dairy products, has been shown to reduce obesity [47], and prevent cardiovascular [48,49], cancer [50], and overall mortality and morbidity [51,52]. In Italy, the level of adherence to the Mediterranean diet is still relatively high [53]. Also habitual diets of Egypt, Iran, and Japan (i.e.…”
Section: Discussionmentioning
confidence: 99%